Guidelines for predicting lesion size at common endocardial locations during radio-frequency ablation - Tungjitkusolmun, Supan; Vorperian, Vicken R.; Bhavaraju, Naresh; Cao, Hong; Tsai, Jang Zern; Webster, John G. (My University, 2001)
We used the finite element method to study the effect of radio-frequency (RF) catheter ablation on tissue heating and lesion formation at different intracardiac sites exposed to different regional blood velocities. We examined the effect of application of RF current in temperature- and power-controlled mode above and beneath the mitral valve annulus where the regional blood velocities are high and low respectively. We found that for temperature -controlled ablation, more power was delivered to maintain the preset tip temperature at sites of high local blood velocity than at sites of low local blood velocity. This induced more tissue heating and larger lesion volumes than ablations at low velocity regions. In contrast, for power-controlled ablation, tissue heating was less at sites of high compared with low local blood velocity for the same RF power setting. This resulted in smaller lesion volumes at sites of low local velocity. Our numerical analyzes showed that during temperature-controlled ablation at 60 °C, the lesion volumes at sites above and underneath the mitral valve were comparable when the duration of RF current application was 10 s. When the duration of RF application was extended to 60 s and 120 s, lesion volumes were 33.3% and 49.4% larger above the mitral valve than underneath the mitral valve. Also, with temperature-controlled ablation, tip temperature settings of 70 °C or greater were associated with a risk of tissue overheating during long ablations at high local blood velocity sites. In power-controlled ablation (20 W), the lesion volume formed underneath the mitral valve was 165.7% larger than the lesion volume above the mitral valve after 10 s of ablation. We summarized the guidelines for energy application at low and high flow regions.
Keywords: Cardiac ablation; Catheter ablation; Finite element; Power-controlled; Radio-frequency ablation; Temperature-controlled